KEANEKARAGAMAN MOLUSKA TERESTRIAL DI JALUR PENDAKIAN SELO TAMAN NASIONAL GUNUNG MERBABU, KABUPATEN BOYOLALI, JAWA TENGAH - Larosi Nufikri Garmellia; Jafron Wasiq Hidayat; Fuad Muhammad (Jurnal Akademika Biologi, 2017)
Terrestrial mollusc is one of the most important basic component in a terrestrial ecosystem and has an important role in forest ecosystem. Ecologically, they could be an indicator to determine the habitat.This research located in Taman Nasional Gunung Merbabu especially Selo Track give some informations for biodiversity and conservation purpose. This research was conducted on November 2016 until January 2017. For research method, it usedpurposive sampling method for select survey location and stratified random sampling with diagonal plot area of 10m x 10m for sampling method. The data analysis used Shannon-Wienner diversity index (H’) and evenness index (e).Results found the total species obtained 43 species of 11 Famili. The most Common speciesfound were, Diplommatina perpusilla, Helicarion albellus, Microcystina exigua and Landouria smironensis. Diversity index (H') ranged from 0.75-2.57whichcategorized for low to moderate. Evenness index value (e) range 0,41-0,77 whichcategorized for  moderate to high.  Keyword:Diversity,Terrestrial Mollusks, TNGMb